(3fKQ GddGdFs - (3CHhGdMSf Ydj Hf CHj WGdH Hf YHO GdeWdH,J (B40 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI MQa GdCda EjeGf GdeQA jYQa HGjeGf CNhc hGNGc ai GdTOI s
(3BNQgG (B:s
(3ef BNQ GdehLhO jTgO Ydjce GdcJGH jhe jbhe GdMSGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3hgh efShH ddEeGe Ydi HGYJHGQ Cf Pdc cdg ef Mceg hCbhGdg hPdc ZjQ UMjM HGdcdjIs
(3hgh eQJH Ydi MQha GdeYOe heYg JQLeg dHYVg HGdaGQSjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B295s
Keywords: (3eJaQbGJs